Solid phase extraction of lead in water using triethylenetetramine-modified resin for determination by UV-visible and atomic spectrometries - Nuttiga Ngamkitpinyo (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 2010